Exploring the role of aging in the relationship between obstructive sleep apnea syndrome and osteoarthritis: Insights from NHANES data - Luo, Xin; Chen, Minghong; Xu, Jinghong (Frontiers in Medicine, 2024)
Background Osteoarthritis (OA) is characterized by high morbidity and disability. While studies have demonstrated that OA is correlated with age-related diseases, few have shown the potential relationship between OA and obstructive sleep apnea syndrome (OSAS). OSAS is characterized by intermittent hypoxia and hypercapnia. We hypothesize that these stressors induce aging and increase the prevalence of OA. Methods The study included 10,641 participants drawn from the National Health and Nutrition Examination Survey (NHANES) dataset during 2005–2008 and 2015–2018. The correlation between OSAS and OA was analyzed using multivariable logistic regression, aging-related biomarkers were calculated, and the role of aging was explored through mediation analysis. Results OSAS was associated with an elevated risk of OA (for quartile 4 vs. quartile 1, odds ratio (OR) 2.31, 95% confidence interval (CI) 1.34 to 3.99; p-value for the trend = 0.004) after adjusting covariates. In the 20–59 years and > 60 years subgroup, the OSAS patients showed a similar trend (for quartile 4 vs. quartile 1, OR 5.69, 95% CI 2.75 to 11.8; p-value for the trend <0.001; OR 2.42, 95% CI 1.23 to 4.76; p-value for the trend = 0.004, respectively). Further mediation analysis revealed that aging acted as a mediator between OA and OSAS. The mediation proportions for biological age (BA) and phenotypic age (PA) were 13.82 and 52.94%, respectively, both with p < 0.001. Conclusion These findings suggest that individuals with OSAS may have an increased prevalence of OA, with aging also being involved in the association.